Anatomical retinaculum repair and pseudo-pouch closure: surgical technique for management of posterior tibial tendon dislocations - Seiça, Emanuel Cortesão; Gamelas, João; Canhoto, Joana; Vide, João; Cardoso, Afonso (International Journal of Research in Orthopaedics, 2024)
This study aims to present a surgical technique for managing Type-II posterior tibial tendon (PTT) dislocations, characterized by a detachment of both the flexor retinaculum and periosteum from the tibia, and to review existing literature on treatment approaches for this rare condition. We describe a surgical procedure that involves an approach to the PTT, assessment, and potential deepening of the retro malleolar groove, and repair of the detached flexor retinaculum using a double suture technique. The technique addresses the challenges posed by the pseudo pouch formed due to the detachment and aims to stabilize the PTT within the groove. The surgical outcomes of two cases involving young, active patients are discussed, including pre- and post-operative assessments. In case 1, a 19-year-old male athlete demonstrated improvement in pain and function, with no recurrence of dislocation at six months follow-up. Case 2, a 40-year-old male athlete, experienced slight discomfort but returned to practice with improved strength and function. Both cases showed effective tendon stabilization within the retro malleolar groove and favorable outcomes without significant complications. The described surgical technique for Type-II PTT dislocations, involving reattachment and repair of the retinaculum, successfully addresses the challenges of the pseudo pouch and provides effective stabilization of the tendon. This approach results in satisfactory clinical and radiological outcomes, with most patients achieving a return to pre-injury function. The study highlights the need for further research to compare biomechanical effectiveness and long-term tissue healing outcomes of this technique.